"Through the kaleidoscope": Intersections between theoretical perspectives and classroom implications in Critical Global Citizenship Education - Eidoo, Sameena; Ingram, Leigh-Anne; MacDonald, Angela; Nabavi, Maryam; Pashby, Karen; Stille, Saskia (Canadian Journal of Education/Revue canadienne de l'éducation, 2012)
This paper presents a multi-voiced examination of educating for global citizenship from critical, interdisciplinary perspectives. The paper explores how insights from theoretical work on multiculturalism, race, religion, gender, language and literacy, and eco-justice can contribute to a critical global citizenship education practice. It reports the learning of a group of six Canadian PhD Candidates, who engaged in a year-long collaborative process to explore critical approaches to global citizenship education by focusing on key intersecting concerns, particularly critically understanding globalization. Drawing on theoretical considerations and discussions, the authors consider pedagogical implications for classroom teaching and learning.